Globalization and rural poverty - Pranab Bardhan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
In this paper we provide an analytical account of the mechanisms through which globalization, in the sense of increased foreign trade and long-term capital flows, affects the lives of the rural poor in developing countries (in their capacity as workers, consumers, recipients of public services or users of common property resources). Globalization can cause many hardships for the rural poor, but it also opens up some opportunities which some countries can utilize and others do not, largely depending on their domestic political and economic institutions, and the net outcome is often quite complex and almost always context-dependent, belying the glib pronouncements for or against globalization made in the opposing camps.
Keywords: F1; O1; Q1; 330; absolute poverty; self-employed; wage-employed; trade liberalization; Landbevölkerung; Ländliche Armut; Globalsteuerung; Direktinvestition; Kapitalmobilität; Entwicklungsländer